Multivariate analysis of factors related to radiographic knee osteoarthritis based on the comparison between football players and matched nonsportsmen - Lv, Hongzhi; Chen, Wei; Yuwen, Peizhi; Yang, Na; Yan, Xiaoli; Zhang, Yingze (International orthopaedics, 2018)
Purpose Knee osteoarthritis (KOA) is the most common joint pathology worldwide and a major cause of later disability. It is unknown if the bone mass density (BMD) is correlated with KOA. This study aimed to investigate the prevalence of radiographic KOA among retired professional football players by comparing with matched nonsportsmen, and assess the correlation between BMD and KOA. Methods A cross-sectional, descriptive study was performed on a group of retired professional football players without history of knee injury. A control group of nonsporting volunteers was matched to the football player group in terms of age, height, weight, and body mass index (BMI). Uni- and multivariate analyses were performed to identify risk factors for KOA and predictors for knee function. Results Eighty-six retired male professional football players, with a mean age of 53 (51–58) years and an average period of professional career of 19.8 ± 6.3 years, were enrolled into the study group. Eighty-six subjects were included in the control group. Radiographic KOA was more common in the control group (45.3%) than in the study group (15.1%; χ 2 = 18.633, P < 0.001). While the HSS, IKS score, and BMD of spine, femoral neck, and trochanter were all higher among sportsmen than the nonsportsmen ( z = 10.250, z = 10.450, z = 7.237, z = 8.826, z = 8.776, all P < 0.001). Independent risk factors for ROA were age (55–60 + years, aOR 9.159, P < 0.001) and BMD (decrease, aOR 16.226, P = 0.001; osteoporosis, aOR 8.176, P = 0.005). The mathematical model of multiple linear regression for the HSS and IKS score were Y = 127.217–3.334 age + 8.971 BMD + 4.752 occupation and Y = 57.784–3.022 age + 7.241 BMD + 4.730 occupation, respectively. Conclusions This study reveals that low BMD and advanced age are independent risk factors for KOA. High BMD and regular exercise have a positive impact on knee function as evaluated with the use of HSS and IKS. Our findings guarantee further study to investigate the possibility that KOA may be caused by low BMD.